Pilot Allocation Scheme for Pseudo-random Sequence Scrambling in Massive MIMO System - HAN Zhi-yu; DONG Jing-wei; YAN Ning; WANG Xin; LI Jia (Journal of Harbin University of Science and Technology)
In this paper，a scheme of joint polar coordinate pilot assignment and pseudo-random code pilot design is proposed to solve the pilot contamination caused by the reuse of the same pilot sequence in each cell of the Massive MIMO system. First，all users in each cell were marked with polar coordinates，and pilot sequences were allocated according to the size of the user's polar angle. Then，pseudo-random codes with different time delays were used to disturb to users using the same pilot sequence in different cells，so as to improve the accuracy of channel estimation. Through theoretical derivation and data simulation analysis，the scheme can effectively reduce the minimum mean square error of channel estimation and improve the signal-to-noise ratio and average transmission rate of uplink transmission. Thus the adverse effect of pilot contamination on channel estimation is reduced and the channel throughput is improved.